Psychophysical demonstration of bidirectional pain modulation (sensitization and desensitization) by ascending or descending progressions of thermal stimulus intensity - Vierck, Charles J.; Riley, Joseph L.; Wong, Fong; King, Christopher D.; Mauderli, Andre P. (Brain research, 2010)
A psychophysical method of response-dependent stimulation presented ascending and descending series of thermal stimulus intensities that maintained an average rating (setpoint) of mild pain (20 on a scale of 0–100) or moderate pain (35). Subjects were presented with alternating series of thermal stimuli that increased until ratings reached or exceeded the setpoint, then decreased until ratings equaled or were less than the setpoint, then increased, etc. Plots of pain intensity ratings differed substantially for series of ascending and descending stimulus intensities. After an ascending series, pain ratings during a descending series were higher than predicted, and after a descending series, pain ratings during an ascending series were lower than predicted. Thus, the nervous system detects and discriminates between ascending and descending trends in stimulus intensity and alters the magnitude of pain sensations in the direction of the trend of increasing or decreasing stimulus intensity. Ascending (sensitizing) trend effects may increase the magnitude of pathological pain in the absence of treatment, and descending (desensitizing) trend effects likely would enhance the efficacy of procedures that reduce pain sensitivity.